An Arduino-Based Robot for Teaching Drawing and Painting (Innovative Applications of AI, 2024)
This paper presents a novel drawing robot system centered around an Arduino platform, which employs clips to attach two motors to a whiteboard. Ropes are wound around the motors and connected to a pen holder, with the other ends wound on spool reels, driven by stepper motors to control the drawing by either letting out or retracting the lines. The system incorporates a camera linked to a Raspberry Pi and Arduino, which, after recognizing images, replicates the corresponding patterns on the whiteboard. Our device facilitates a more naturalistic human-computer interaction for educational purposes, enabling the drawing robot to guide children in creating artwork on the whiteboard and to assist art teachers in their instruction.